Hard-to-recover reserves of Yugra oil (West Siberia) - Isaev, V.I.; Kuzmenkov, S.G.; Ayupov, R.Sh.; Kuzmin, Yu.A.; Lobova, G.A.; Stulov, P.A. (Геофизический журнал, 2019)
Criteria of hard-to-recover reserves, results and opportunities of their using for development in the conditions of Yugra fields are analyzed in the article. В статье анализируются критерии трудноизвлекаемых запасов, результаты и возможности их использования для разработки в условиях югорских месторождений. У статті аналізуються критерії важко видобувних запасів, результати і можливості їх використання для розробки в умовах Югорський родовищ.